Heat shock protein 90α-dependent B-cell-2-associated transcription factor 1 promotes hepatocellular carcinoma proliferation by regulating MYC proto-oncogene c-MYC mRNA stability - Zhou, Xueqiong; Mayer, Matthias P. (Hepatology, 2019)
B-cell lymphoma 2 (Bcl-2)-associated transcription factor 1 (Bclaf1) is known to be involved in diverse biological processes, but, to date, there has been no evidence for any functional role of Bclaf1 in hepatocellular carcinoma (HCC) progression. Here, we demonstrate that Bclaf1 is frequently up-regulated in HCC and that Bclaf1 up-regulation is associated with Edmondson grade, lower overall survival rates, and poor prognosis. Overexpression of Bclaf1 in HCC cell lines HepG2 and Huh7 promoted proliferation considerably, whereas Bclaf1 knockdown had the opposite effect. Xenograft tumors grown from Bclaf1 knockdown Huh7 cells had smaller tumor volumes than tumors grown from control cells. Furthermore, our study describes MYC proto-oncogene (c-Myc) as a downstream target of Bclaf1, given that Bclaf1 regulates c-MYC expression posttranscriptionally by its RS domain. To exert this function, Bclaf1 must interact with the molecular chaperone, heat shock protein 90 alpha (Hsp90α). In HCC tissue samples, Hsp90α levels were also increased significantly and Hsp90α-Bclaf1 interaction was enhanced. Bclaf1 interacts with the C-terminal domain of Hsp90α, and this interaction is disrupted by the C-terminal domain inhibitor, novobiocin (NB), resulting in proteasome-dependent degradation of Bclaf1. Moreover, NB-induced disruption of Hsp90α-Bclaf1 interaction dampened the production of mature c-MYC mRNA and attenuated tumor cell growth in vitro and in vivo. Conclusion: Our findings suggest that Bclaf1 affects HCC progression by manipulating c-MYC mRNA stability and that the Hsp90α/Bclaf1/c-Myc axis might be a potential target for therapeutic intervention in HCC.
First published: 17 July 2018
Gesehen am 21.05.2019